P.227 Investigating the changes in ITP after CSF drainage in patients with acute traumatic SCI: Results from a Quaternary Spinal Care Center. (November 2021) - Hindi, MN; Gee, CM; Paquette, S; Ailon, T; Dvorak, M; Dea, N; Charest-Morin, R; Fisher, C; Street, J; Boyd, M; Tsang, A; Belanger, L; et al.
Abstract : Background: Mean arterial pressure augmentation is one current established practice for management of patients with SCI. We present the first data investigating the effectiveness of Intrathecal Pressure (ITP) reduction through CSF drainage (CSFD) in managing patients with acute traumatic SCI at a large academic center. Methods: Data from 6 patients with acute traumatic SCI were included. A lumbar intrathecal catheter was used to monitor ITP and volume of CSFD. CSFD was performed and recorded hourly. ITP recordings were collected hourly and the change in ITP was calculated (hour after minus before CSFD). 369 data points were collected and change in ITP was plotted against volume of CSFD. Results: Data across all patients showed variability in the ITP over time without a significant trend (slope=0.016). We found no significant change in ITP with varying amounts of CSFD (slope=0.007, r 2 =0.00, p=0.88). Changes in ITP were not significantly different across groups of CSFD but the variation in the data decreased with increasing levels of CSFD. Conclusions: We present the first known data on changes in ITP with varying degrees of CSFD in patients with acute traumatic SCI. These results may provide insight into the complexity of ITP changes in patients post-injury and help inform future SCI management.